4D printing of shape memory polylactic acid beams: An experimental investigation into FDM additive manufacturing process parameters, mathematical modeling, and optimization. (6th January 2023) - Hosseinzadeh, M.; Ghoreishi, M.; Narooei, K.
Abstract: 4D printing is a novel process, which is referred to as the future of additive manufacturing. The main goal of 4D printing is to control the final shape in terms of quality (type of deformation) and quantity (amount of deformation) over time. In this study, the response surface method (RSM) has been used to develop a model for controlling the amount of Polylactic acids (PLA) torsional and flexural deformation in 4D printing. The model examines the effect of FDM parameters such as layer height, print speed, and nozzle diameter. Using the central composite design (CCD), high-order models were developed to calculate the optimum operating conditions with high accuracy compared to the experimental results. By achieving optimum printing conditions, the maximum amount of torsional and flexural deformation was achieved. The values of layer height, print speed, and nozzle diameter for both flexural and torsional modes were 0.05 mm, 112 mm/s, and 0.4 mm, respectively. Graphical abstract: Unlabelled Image Highlights: 4D printing of shape memory PLA beams was investigated both experimentally and numerically. Response surface method was used to develop a model for controlling the amount of deformation. The effects of FDM parameters such as layer height, print speed, and nozzle diameter of PLA were studied in detail. To achieve the maximum amount of torsional and flexural deformations, the optimum operating conditions were presented.